A new method for determining the reactions of mechanical constraints - Do Sanh; Do Dang Khoa (Vietnam Journal of Mechanics, 2006)
In the present paper it is introduced the method for determining the reactions of mechanical constraints (holonomic and nonholonomic constraints).